2022
DOI: 10.1021/acs.jpca.1c10679
|View full text |Cite
|
Sign up to set email alerts
|

Planar Networks of Boron Triangles: Analogies to Benzene and Other Planar Aromatic Hydrocarbons

Abstract: The lowest energy structures for B n species (n = 6 to 23 except for 20) observed experimentally in the gas phase with a mass spectrometer are planar networks of boron triangles. Such networks are considered to consist of trigonal planar sp 2 -hybridized boron atoms having perpendicular p orbitals similar to the carbon atoms in benzene and other planar aromatic hydrocarbons. Electron bookkeeping for reasonable chemical bonding topologies of wheel-like structures such as B@B n−1 (n = 6−9) leads to two π-electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Although the geometries of the B 15 cluster in the cationic, neutral and anionic states have extensively been determined in previous studies, [12][13][14][15][16][19][20][21][22] we would take this opportunity to explore them again using different quantum chemical methods. The lower-lying isomers are separately searched in each charge state.…”
Section: Methodsmentioning
confidence: 99%
“…Although the geometries of the B 15 cluster in the cationic, neutral and anionic states have extensively been determined in previous studies, [12][13][14][15][16][19][20][21][22] we would take this opportunity to explore them again using different quantum chemical methods. The lower-lying isomers are separately searched in each charge state.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang and co-workers have found that, on the silver substrate, some specific types of borophene edges are very stable and might be self-passivated as the interaction between the borophene edge and the substrate is very weak . Some theoretical studies have proposed similar chemical bonding models with peripheral two-center two-electron (2c–2e) and central three-center two-electron (3c–2e) bonds for planar boron nanoclusters, showing different bonding configurations at the edge and bulk of 2D boron materials. , Unfortunately, an insightful understanding of the superior stability of the borophene edge or the mechanism of dangling orbital self-termination at the edge is still missing.…”
Section: Introductionmentioning
confidence: 99%
“… 17 Some theoretical studies have proposed similar chemical bonding models with peripheral two-center two-electron (2c–2e) and central three-center two-electron (3c–2e) bonds for planar boron nanoclusters, showing different bonding configurations at the edge and bulk of 2D boron materials. 18 , 19 Unfortunately, an insightful understanding of the superior stability of the borophene edge or the mechanism of dangling orbital self-termination at the edge is still missing.…”
Section: Introductionmentioning
confidence: 99%